2011
DOI: 10.1111/j.1469-0691.2010.03348.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use in adult outpatients in Switzerland in relation to regions, seasonality and point of care tests

Abstract: The use of antibiotics is highest in primary care and directly associated with antibiotic resistance in the community. We assessed regional variations in antibiotic use in primary care in Switzerland and explored prescription patterns in relation to the use of point of care tests. Defined daily doses of antibiotics per 1000 inhabitants (DDD(1000pd) ) were calculated for the year 2007 from reimbursement data of the largest Swiss health insurer, based on the anatomic therapeutic chemical classification and the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 21 publications
7
38
1
2
Order By: Relevance
“…Seasonal variation in the prescribing of antibiotics has been reported in Europe (16,27), Canada (28), and Israel (29) and, recently, in the United States (15). In the European and Canadian studies, the increase in antibiotic use in the winter months ranged from 21% to 42% (16,(27)(28)(29), in similarity to the results found here.…”
Section: Discussionsupporting
confidence: 79%
“…Seasonal variation in the prescribing of antibiotics has been reported in Europe (16,27), Canada (28), and Israel (29) and, recently, in the United States (15). In the European and Canadian studies, the increase in antibiotic use in the winter months ranged from 21% to 42% (16,(27)(28)(29), in similarity to the results found here.…”
Section: Discussionsupporting
confidence: 79%
“…A low seasonal variation together with a low use has been connected to appropriate use of antibiotics and low antimicrobial resistance rates (2,9,10). In the present study, Mexico and Brazil showed seasonal variations in the use of penicillins with a higher use in autumn and winter than in summer.…”
Section: Discussionmentioning
confidence: 65%
“…An interesting finding in the previous evaluation was that seasonal variation appeared to change after the restrictions took place, but this was not explored in more detail. Seasonal variation in antibiotic use has been associated with short-term lowering of resistance rates in the United States (7) and Israel (8); moreover, low seasonal variation has been related to appropriate-use profiles in Europe (9,10). Furthermore, it has been suggested that a better understanding of seasonal variation of antibiotic prescribing can be useful in the design of interventions to reduce inappropriate use of antibiotics (11).…”
mentioning
confidence: 99%
“…In the US, the top five list of prescribed antibiotics included azithromycin, amoxicillin, amoxicillin/clavulanic acid, ciprofloxacin and cefalexin in 2010 [24], which is similar to our results. In Switzerland, amoxicillin and amoxicillin/clavulanic acid were the most used antibiotics for outpatients, with fluoroquinolones and macrolides the second and third most prescribed antibiotics in 2007 [15]. In Germany most common antibiotics consumed were penicillin/ amoxicillin, followed by tetracyclines and newer macrolides (roxithromycin, azithromycin and clarithromycin) in 2003 [17].…”
Section: Discussionmentioning
confidence: 99%
“…A thorough understanding of antibiotic prescribing patterns can help policy makers identify areas where potentially unnecessary costs can be avoided. Although data on antibiotic prescribing patterns are available for several European countries [15][16][17][18][19][20][21][22], such data are limited for Greece [13].…”
Section: Introductionmentioning
confidence: 99%